Son of a Red Devil - Gelindo, Lukemba (Book collections on Project MUSE., 2013)
This is the story of Lukemba Gelindo. He was adopted by a former football player, August Hellemans - also called Gustaf - of the national Belgian team - The Red Devils. Gelindo and his brother were adopted after they were abandoned in a nursery home where they had been mistreated. He grew up in a Flemish village where people had never seen a black person. In general, Flemings are still surprised when they hear blacks speaking their language fluently. This can lead to perplexing and frustrating encounters with ignorance and arrogance, such as during a job interview where Gelindo had to justify himself over and over again as to where he learned to speak the Flemish language. This is also the story of the differences in mentality between the Flemings and Walloons viewed from a black perspective through the eyes of someone who is intimately familiar with both cultures. Gelindo's parents were Flemings but he always went to French speaking schools. It is as well, a story about racism, especially racism that stems from Flemings - which is quite implacable, to say the least. Evidence of this statement is not far-fetched; black people are completely absent in the Flemish media, except perhaps as footballers or musicians, meant to entertain but not to claim rights, entitlements or any serious measure of social visibility. More personally, this story is about Gelindo's experience undergoing psychiatric treatment and also about the sexual tensions between his mother and him. Among other things, it is also Gelindo's aim to speak out against the manner in which young black children get objectified by the rich and famous as the latest 'must have' things, designer accessories up for adoption and adaptation. Like in the rest of the world, this trend is also seen in Flemish magazines in which parents pose in photos with their little black trophy children. The account is direct, honest, uncompromising, laced with cynicism, and in many ways therapeutic.